2017
DOI: 10.11604/pamj.2017.28.9.11315
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial localization of Hodgkin's disease

Abstract: The endobronchial localization of Hodgkin's disease is a rare entity which is often confused with endobronchial tuberculosis in our setting. We report the case of a 16 years old female who presented with 6 months history of dry cough, hemoptysis, dyspnea, dysphagia and dysphonia. The chest radiography showed a mediastinal and pulmonary opacity. The chest CT scan found enlarged mediastinal lymph nodes. The bronchial biopsy and peripheral lymph node biopsy confirmed Hodgkin's disease with endobronchial localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Various reports have indicated that the prevalence of cryptosporidiosis ranges from 6.25 to 39.65% in cattle in different parts of the world [ 12 14 ]. There are various factors that affect the prevalence of cryptosporidiosis including age, bedding type, hygiene, colostrum feeding, management practices, feed and water sources, diarrhoea and climate [ 15 ]. In Ethiopia, where over 50 million cattle are raised under various agro-ecological zones, a few research works have been done on bovine cryptosporidiosis in central parts of the country reporting a prevalence ranges from 2.3 to 27.8% [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various reports have indicated that the prevalence of cryptosporidiosis ranges from 6.25 to 39.65% in cattle in different parts of the world [ 12 14 ]. There are various factors that affect the prevalence of cryptosporidiosis including age, bedding type, hygiene, colostrum feeding, management practices, feed and water sources, diarrhoea and climate [ 15 ]. In Ethiopia, where over 50 million cattle are raised under various agro-ecological zones, a few research works have been done on bovine cryptosporidiosis in central parts of the country reporting a prevalence ranges from 2.3 to 27.8% [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent presentation of HL is a bulky mediastinal mass, constituting the 67–87% of cases [7]. Conversely, pulmonary HL involvement is a less common presentation and can be seen in lymph nodes, parenchyma, and tracheobronchial tree, usually in association with hilar or mediastinal adenopathy [1, 8].…”
Section: Discussionmentioning
confidence: 99%